Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s11356-014-3036-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of organic pollutants in saline wastewater by halophilic microorganisms: a review

Abstract: Agro-food, petroleum, textile, and leather industries generate saline wastewater with a high content of organic pollutants such as aromatic hydrocarbons, phenols, nitroaromatics, and azo dyes. Halophilic microorganisms are of increasing interest in industrial waste treatment, due to their ability to degrade hazardous substances efficiently under high salt conditions. However, their full potential remains unexplored. The isolation and identification of halophilic and halotolerant microorganisms from geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(52 citation statements)
references
References 81 publications
1
47
1
1
Order By: Relevance
“…An efficient utilization of microbes for wastewater treatment can be difficult due to characteristics of wastewater, such as salinity. It has been found that salinity affects microbial communities in wastewater treatment bioreactors in different ways, such as increasing mortality rate due to differential osmotic pressure across cell membranes, inhibition of biodegradation of toxic metabolic intermediate compounds, and reduction of bioavailability of substrates, among others . Urban wastewater usually has a salinity level between the 0.7 and 3.0 mS cm −1 measured as electric conductivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficient utilization of microbes for wastewater treatment can be difficult due to characteristics of wastewater, such as salinity. It has been found that salinity affects microbial communities in wastewater treatment bioreactors in different ways, such as increasing mortality rate due to differential osmotic pressure across cell membranes, inhibition of biodegradation of toxic metabolic intermediate compounds, and reduction of bioavailability of substrates, among others . Urban wastewater usually has a salinity level between the 0.7 and 3.0 mS cm −1 measured as electric conductivity .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that salinity affects microbial communities in wastewater treatment bioreactors in different ways, such as increasing mortality rate due to differential osmotic pressure across cell membranes, inhibition of biodegradation of toxic metabolic intermediate compounds, and reduction of bioavailability of substrates, among others. 1,2 Urban wastewater usually has a salinity level between the 0.7 and 3.0 mS cm 21 measured as electric conductivity. 3 Nevertheless, there are many industrial processes and human activities that produce wastewater of higher salinity, such as seafood processing, utilization of seawater for toilet flushing, snow-melting strategies in human settlements, or legal or illegal disposal of flowback from gas drilling procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that salinity decreases the microbial activity of microorganisms, but however this limitation can be overcome by adaptation . Treatment of high‐salinity wastewater showed that ammonium was predominantly removed by ammonium oxidizing archaea (AOA) and ammonium oxidizing bacteria (AOB), with a clear domination of archaea over bacteria in terms of total 16S rRNA gene copy number .…”
Section: Resultsmentioning
confidence: 99%
“…36 It has been reported that salinity decreases the microbial activity of microorganisms, but however this limitation can be overcome by adaptation. 37 Treatment of high-salinity wastewater showed that ammonium was predominantly removed by ammonium oxidizing archaea (AOA) and ammonium oxidizing bacteria (AOB), with a clear domination of archaea over bacteria in terms of total 16S rRNA gene copy number. 38 This result could happen also under the variable salinity conditions, and therefore more research should be conducted on competition of AOA and AOB for the treatment of variable salinity wastewater.…”
Section: Performance Of the Bioreactors For The Treatment Of Variablementioning
confidence: 99%
“…Recent advancements have also proven successful via the addition of matched microbial strains to the medium to enhance the resident microbe's population ability to break down contaminants. Microorganisms used to perform the function of bioremediation are known as bioremediators [7]. Remediation is to find a remedy for neutralizing a toxin using living things due to their metabolic activity.…”
Section: Introductionmentioning
confidence: 99%